Fatores associados ao desempenho dos concluintes de cursos de engenharia no ENADE 2011 - Gabriela Miranda Moriconi; Paulo A. Meyer M. Nascimento (Instituto de Pesquisa Econômica Aplicada (IPEA), 2014)
– This paper applies multilevel models to Brazilian's tertiary education assessment data in order to test whether some of the factors pointed out by the literature as relevant to achievement are associated with the performance of last year engineering students in 2011. Brazil is the only country where compulsory national exams are applied to last year tertiary education students. This sets a unique opportunity to model student achievement on tertiary education as a function of discretionary and non-discretionary factors. Results confirm that selective courses produce better-prepared graduates, but also show that out-of-class availability of teachers is positively associated to performance in most types of engineering courses, and well-designed teaching-and-learning plans seem to be particularly relevant for industrial students. In average, students coming from publicly run secondary schools and attaining engineering courses in the appropriate age perform better, but women and non-whites still achieve lower grades than white men.
Keywords: I21; I23; C51; 330; student achievement; engineering education; associated factors